The Art of 3-D : computer animation and imaging - Kerlow, Isaac Victor, 1958- 4 0 16; 5 (New York : John Wiley & Sons, 2000)
Explains each step in the process of creating three-dimensional computer still images and animation, and includes illustrations, diagrams, and a guide to Internet resources.
Includes index.;Rev. ed. of: The art of 3-D computer animation and imaging. New York : Van Nostrand Reinhold, c1996.
Keywords: 2 -- 0; 6; Computer graphics.;Computer animation.;Three-dimensional display systems.;Computer graphics.;Computer animation.;Three-dimensional display systems; 20; 2